Предмет: Математика,
автор: samoilovvadim23
6) (1-cos 2a) tg (п+a)
Ответы
Автор ответа:
0
Відповідь:
1 - cos 2a = 2 sin^2 a
(1-cos 2a) tg (п+a) = 2 sin^2 a tg (п+a)
tg (a + b) = (tg a + tg b)/(1 - tg a tg b)
tg (п+a) = (tg п + tg a)/(1 - tg п tg a)
(1-cos 2a) tg (п+a) = 2 sin^2 a (tg п + tg a)/(1 - tg п tg a)
Удачи!
Покрокове пояснення:
Похожие вопросы
Предмет: История,
автор: Аноним
Предмет: Биология,
автор: Oleg6617
Предмет: Українська література,
автор: wainbaum
Предмет: Українська мова,
автор: Viki4y